Analysis of Social Values ​​in the Somat Family Cartoon Show Episode “Dudung Is Lost” - Syifa Fauzia (LADU: Journal of Languages and Education, 2022)
Background: Social value is a valuable thing that has to do with the interrelationships and relationships between individuals and other individuals. As social creatures, interaction activities are well adapted and interesting through conventional entertainment media, one of which is cartoon shows. Purpose: The purpose of this study is to find out the social values ​​contained in the "Dudung Is Lost" episode of the Somat Family Cartoon Design and methods: The research method used in this study is a qualitative research with a descriptive qualitative research type. The data analysis applied in this research is using the critical discourse model of Norman Fairclough.. Results: The results of the implementation of this research reveal that there are many social values ​​that can be taken in the Somat Family Cartoon Episode "Dudung Is Lost", including 1) the value of empathy, 2) helping each other, and 3) liking to give advice. These three social values ​​are deliberately included in the Somat Family Cartoon show to provide educational value. Especially when it was disseminated in Indonesia where the majority of the targeted audience were children.